The Materiality of Nothing Exploring Our Everyday Relationships with Objects Absent and Present - Holmes, Helen (Materializing Culture, 2024)
The Materiality of Nothing explores the invisible, intangible and transient materials and objects of everyday life and the relationships we have with them. Drawing on over 15 years of original, empirical research, it builds on growing research on the everyday, and unites the established field of material culture and materiality with emerging sociological studies exploring notions of nothing and the unmarked. The chapters cover topics such as lost property, museum curation, plastic microfibres, thrift, music and even hair, illuminating how invisible and intangible materials conjure memories, meanings and identities, inextricably binding us to other people, places and things. In turn, the book also engages with issues of sustainability and consumption, raising questions regarding society's increasing need for material accumulation and posing some alternatives.